COMPARATIVE ANALYSIS BETWEEN THE NOVEL AND FILM LORD OF THE FLIES USING ENESTE’S ECRANISATION THEORY - Hayati Shofa, Asyida; Fatimah, Nurul; Widyaningrum, Noviana Romadloni (UIN Raden Mas Said Surakarta, 2024)
Ecranisation is a process of finding out the difference between a novel and a film. One of the novels that has been adapted into a film is Lord of the Flies. Furthermore, this research aims to reveal the process of ecranisation between the novel Lord of the Flies (1954) and its film adaptation Lord of the Flies (1990) by William Golding. How are the differences between the novel Lord of the Flies (1954) and its film adaptation Lord of the Flies (1990). In analyzing, the writers use the theory of Ecranisation (1991) from Pamusuk Eneste which is divided into three processes, namely reduction, addition and variation. This research used a descriptive qualitative approach aimed at describing the phenomenon and its characteristics. The data is collected qualitatively by examining them throughout to get relevant issues and ideas and classify them. The results of the analysis reveal that in the film Lord of the Flies (1990), there is a narrowing and expansion of the original storyline, namely the novel Lord of the Flies (1954). This is because it does not take much time when presenting the story of the novel. The writers finds that the ecranisation process that occurs in Lord of the Flies does not change the core of the story, but only refine and beautify the story's fabric. Key words: Ecranisation, Eneste, Lord of the Flies (1954) novel, Lord of the Flies (1990) film